Delayering and Firm Performance: Evidence from Swiss firm-level Data - Dieter Kuhn (University of Basel, Center of Business and Economics (WWZ), 2011)
The past decades witnessed a broad trend towards flatter organizations with less hierarchical layers. A reduction of the number of management levels in a corpora- tion can have both positive and negative effects on firm performance with the net effect being theoretically unclear ex ante. The present study uses a nationally representative data set of firms in Switzerland and empirically examines the di- rect performance effects of delayering. Applying ordinary least squares regressions and propensity score matching, this study finds that delayering significantly increases subsequent firm performance. It can be concluded that flatter hierarchical structures seem to enable firms to better realize their competitive advantage in today's fast moving and knowledge-intensive market environment.
Keywords: 330; Hierarchie; Organisatorischer Wandel; Dezentrale Organisation; Unternehmensorganisation; Unternehmenserfolg; Schweiz